Policy effectiveness evaluation of rural environmental sanitation governance in China: based on the PMC index model - Yingda Xu (Frontiers in Public Health)
BackgroundRural environmental sanitation governance is of vital importance for improving rural living standards and narrowing urban-rural gaps in China. However, the effectiveness of existing policies remains suboptimal due to structural design flaws, highlighting the need for systematic evaluation to address these issues.MethodsThis study integrates the “Policy Modeling Consistency (PMC-Index)” with text-mining technology to quantitatively assess 24 local policies from 7 Chinese cities, with 7 representative samples selected via stratified sampling. The evaluation framework comprises 9 primary variables and 37 subvariables, systematically analyzing the integrity of policy texts through a structured approach.ResultsThe findings reveal an average PMC index of 6.03 across the policies. Specifically, 1 policy is rated “excellent”, 4 “good”, and 2 “unsatisfactory”. Key deficiencies are identified in X1 (Policy Nature), X2 (Policy Timeliness), X5 (Policy Targets), and X7 (Policy Functions), indicating challenges such as insufficient feedback mechanisms, lack of mid-term planning, and limited stakeholder inclusivity.ConclusionThis study conducts a quantitative evaluation of rural environmental sanitation governance policies in 7 Chinese cities. Although the overall content design of these policies is basically reasonable, obvious deficiencies exist. To enhance policy effectiveness, it is necessary to construct a holistic framework integrating dynamic adjustment mechanisms and multi-stakeholder collaboration.